Functionalization of Enzymatically Synthesized Rigid Poly(itaconate)s via Post-Polymerization aza-Michael Addition of Primary Amines - GUARNERI, ALICE; Viola Cutifani; Marco Cespugli; Alessandro Pellis; Roberta Vassallo; Fioretta Asaro; Cynthia Ebert; Lucia Gardossi (Advanced Synthesis & Catalysis, 2019)
The bulky 1,4-cyclohexanedimethanol was used as co-monomer for introducing rigidity in lipase synthetized poly(itaconates). Poly(1,4-cyclohexanedimethanol itaconate) was synthetized on a 14 g scale at 50°C, under solvent-free conditions and 70 mbar using only 135 Units of lipase B from Candida antarctica per gram of monomer. The mild conditions preserved the labile vinyl group of itaconic acid and avoided the decomposition of 1,4-cyclohexanedimethanol observed in chemical polycondensation. Experimental and computational data show that the enzymatic polycondensation proceeds despite the low reactivity of C1 of itaconic acid. The rigid poly(1,4-cyclohexanedimethanol itaconate) was investigated in the context of aza-Michael addition of hexamethylenediamine and 2-phenylethylamine to the vinyl moiety. The enzymatically synthesized linear poly(1,4-butylene itaconate) was studied as a comparison. The two oligoesters (Molecular Weights ranging from 720 to 2859 g mol-1) reacted on a gram scale, at 40-50°C, at atmospheric pressure and in solvent-free conditions. The addition of primary amines led to amine-functionalized oligoesters but also to chain degradation, and the reactivity of the poly(itaconate)s was influenced by the rigidity of the polymer chain. Upon the formation of the secondary amine adduct, the linear poly(1,4-butylene itaconate) undergoes fast intramolecular cyclization and subsequent degradation via pyrrolidone formation, especially in the presence of hexamethylenediamine. On the contrary, the bulky 1,4-cyclohexanedimethanol confers rigidity to poly(1,4-cyclohexanedimethanol itaconate), which hampers the intramolecular cyclization. Also the bulkiness of the amine and the use of solvent emerged as factors that affect the reactivity of poly(itaconate)s. Therefore, the possibility to insert discrete units of itaconic acid in oligoesters using biocatalysts under solvent-free mild conditions opens new routes for the generation of bio-based functional polymers or amine-triggered degradable materials, as a ...